Moderasi Berpikir untuk Menempati Tingkatan Spiritual Tertinggi dalam Beragama - Nirwani Jumala (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2019)
The development of spiritual character is an appropriate step to realize moderation in religion. Spiritual character holds the value of self-awareness about human origin, purpose and destiny while religion is a testimony of faith that people accept as the absolute truth of life upon living on earth. Spirituality provides answers to who we are and how we exist and are aware of our existence, while religion provides answers to what we must reflect in our behavior and actions. Every religion presents a path to spiritual. Following the same religion, doesn't necessarily guarantee that they would have the same path or spiritual level. In fact, they can have a different spiritual value in their religious paths. Religion is not the same as spirituality, but it is a form of spirituality that lives in human's personal and communal civilizations. A Muslim can occupy seven levels of human spirituality from selfish to holiness according to Allah's command. This level consists of nafsu al-amᾱrah, nafsu al-lawwᾱmah, nafsu al-mulhimma, nafsu al-muṭma’innah, nafsu ar-raḍiyah, nafsu al-marḍiah dan nafsu as-safῑyah